Problem-based learning augmented reality based on local potential to improve student learning motivation - Zufahmi Zufahmi; Fatchur Rohman; Dwi Listyorini (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2026)
Advances in technology and information have compelled the education sector to undergo continuous transformation. These developments present new challenges, as educational systems are required to equip students with the knowledge, skills, and attitudes necessary to respond to an increasingly dynamic world. Such competencies are strongly influenced by students’ learning motivation; however, empirical evidence indicates that students’ learning motivation remains relatively low. The present study seeks to examine the effectiveness of an augmented reality–assisted problem-based learning model integrated with local potential in enhancing students’ learning motivation. A quasi-experimental design with a non-equivalent control group was employed. Data on learning motivation were collected using the Motivated Strategies for Learning Questionnaire. The results of the ANCOVA analysis revealed a significant effect on students’ learning motivation (p < 0.05), indicating that the local potential–based AR-PBL model was effective in improving learning motivation. The Partial Eta Squared value of 0.605 indicates a large effect size, accounting for approximately 60% of the variance. Furthermore, the corrected mean score of learning motivation in the experimental group (87.93) was higher than that of the control group (80.64). These findings demonstrate that the local potential–based AR-PBL model is more effective in enhancing students’ learning motivation than the PBL model alone.Abstrak. Kemajuan teknologi dan informasi telah memaksa sektor pendidikan untuk terus melakukan transformasi. Perkembangan ini menghadirkan tantangan baru, karena sistem pendidikan diharuskan untuk membekali siswa dengan pengetahuan, keterampilan, dan sikap yang diperlukan untuk menghadapi dunia yang semakin dinamis. Kompetensi-kompetensi tersebut sangat dipengaruhi oleh motivasi belajar siswa; namun, bukti empiris menunjukkan bahwa motivasi belajar siswa masih relatif rendah. Penelitian ini bertujuan untuk menguji efektivitas model pembelajaran berbasis masalah yang didukung oleh realitas tertambah (augmented reality) yang terintegrasi dengan potensi lokal dalam meningkatkan motivasi belajar siswa. Desain quasi-eksperimental dengan kelompok kontrol non-ekuivalen digunakan. Data motivasi belajar dikumpulkan menggunakan Kuesioner Strategi Motivasi Belajar. Hasil analisis ANCOVA menunjukkan efek signifikan pada motivasi belajar siswa (p < 0.05), menunjukkan bahwa model AR-PBL berbasis potensi lokal efektif dalam meningkatkan motivasi belajar. Nilai Partial Eta Squared sebesar 0.605 menunjukkan ukuran efek yang besar, yang menjelaskan sekitar 60% varians. Selain itu, skor rata-rata yang telah disesuaikan untuk motivasi belajar pada kelompok eksperimen (87.93) lebih tinggi daripada kelompok kontrol (80.64). Temuan ini menunjukkan bahwa model AR-PBL berbasis potensi lokal lebih efektif dalam meningkatkan motivasi belajar siswa dibandingkan dengan model PBL saja.